ANALISIS STRATEGI PENGELOLAAN SAMPAH BERBASIS MASYARAKAT DI DESA LABUHAN SUMBAWA - Pamungkas, Binar Dwiyanto; Ramdani, Erwin (Pusat Riset dan Publikasi, 2024)
The aim of this study was to know the strategies of waste management communities-based in Labuhan Sumbawa Village. This type of research is descriptive research. The data source in this research is primary data. The number of respondents is 30 respondents consisting of bureaucrats, academics and the community. The method used to collect data is by using interviews and documentation. The data analysis tool is by using the Analytic Hierarchy Process (AHP) with the help of expert choice (EC) applications. The results of the study showed that the priority strategies of waste management communities-based in Labuhan Sumbawa village were: 1) Budget, 2) Regulations, 3) Institutions, 4) Infrastructure. The budget placed in the first position in this study means that there were funding support for all activities related to waste management communities-based in Labuhan Sumbawa village, either from the regional, village or third parties in the communities because cleanliness funding was long investment that was able to encourage change in waste management Labuhan Sumbawa village.